Self-Narrative (Re)Construction of Life History through ?Discovering Oneself Again? - Krawczyk-Bocian, Amelia (INSTED: Interdisciplinary Studies in Education & Society, 2019)
The considerations included in the article focus on self-narration that serves life reconstruction in time perspective. Showing the essence and importance of self-narration in the life of a contemporary man directs further thinking to the proposal of reading the author?s narrative technique called as ?discovering oneself again?. The article is an attempt of looking closer at the temporary life history course through self-narration about oneself entangled in daily life.